2015
DOI: 10.1111/jpi.12268
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects porcine oocyte in vitro maturation from heat stress

Abstract: Melatonin is a pleiotropic molecule which plays an important role in animal reproductive activities. Because of the increased global warming, the impact of heat stress (HS) on stockbreeding has become an inevitable issue to be solved. To investigate the potential effects of melatonin on the in vitro maturation of porcine oocyte under the HS, a HS model for porcine oocyte maturation has been used in this study and the different concentrations of melatonin (10(-6) -10(-9)  m) were also tested for their protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 58 publications
8
110
1
Order By: Relevance
“…In agreement with those studies, our results indicated that supplementing melatonin during oocyte maturation improved early embryonic development rates. Melatonin has also been shown to reduce levels of ROS and enhance glutathione production and decrease apoptosis in pig oocytes (Li et al, 2015). Our results agree with this study, as we found supplementation of melatonin to decrease the ROS produced during maturation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with those studies, our results indicated that supplementing melatonin during oocyte maturation improved early embryonic development rates. Melatonin has also been shown to reduce levels of ROS and enhance glutathione production and decrease apoptosis in pig oocytes (Li et al, 2015). Our results agree with this study, as we found supplementation of melatonin to decrease the ROS produced during maturation.…”
Section: Discussionsupporting
confidence: 92%
“…Supplementation of melatonin has shown to lower ROS levels during oocyte maturation in mice (Salehi et al, 2014), bovine (Cebrian-Serrano et al, 2013) and humans (Wei et al, 2013). In pigs, melatonin his been shown to support oocyte maturation and embryo culture (Do et al, 1015) and to protect the oocyte against ROS (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The ROS caused by reproductive ageing is associated with changes in oocyte mitochondrial dynamics and function and mtDNA quantity and prevents oocyte maturation40. It has been reported that heat shock results in an inhibitory effect on porcine oocyte maturation in vitro by improving the ROS in the oocytes41. Maternal-restraint stress increases oocyte aneuploidy by impairing metaphase I spindle assembly and reducing spindle assembly checkpoint proteins in mice42.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin plays key roles in the biologic regulation of circadian rhythms [27,28], sleep [29,30], antioxidant protection [31][32][33][34][35], cell aging [36], tumor growth [12,37], reproduction [31,38], and bone physiology [39,40]. A growing amount of data indicates that the age-related decline in the level of melatonin is closely associated with bone diseases: osteosarcoma, adolescent idiopathic scoliosis and osteoporosis [1,39].…”
Section: Discussionmentioning
confidence: 99%